1997
DOI: 10.1111/j.1600-0684.1997.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for the maturation of protective antibody responses to SIV envelope proteins in experimentally immunized monkeys

Abstract: Studies using live attenuated virus vaccines in the simian immunodeficiency virus (SIV) rhesus macaque model have demonstrated broad protection against experimental challenge. Protection in these studies was found to be critically dependent on the length of time postvaccination, suggesting that protective immunity involves a necessary maturation of immune responses. The current study characterizes the evolution of protective envelope-specific antibody responses from monkeys inoculated with the highly attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Thus, these data indicated a progressive development of protective immunity during the first 6 to 7 months postinfection, suggesting an evolution of virus-specific immune responses to the persistent attenuated EIAV infection. In studies with an attenuated SIV vaccine in monkeys, we have previously reported a protective efficacy of 50% at 3 months postinoculation compared to 100% at 8 months postinoculation (3)(4)(5). Thus, the combined EIAV and SIV attenuated virus vaccine data suggest that the prolonged process for the development of protective vaccine immunity may be a general and distinguishing property of lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these data indicated a progressive development of protective immunity during the first 6 to 7 months postinfection, suggesting an evolution of virus-specific immune responses to the persistent attenuated EIAV infection. In studies with an attenuated SIV vaccine in monkeys, we have previously reported a protective efficacy of 50% at 3 months postinoculation compared to 100% at 8 months postinoculation (3)(4)(5). Thus, the combined EIAV and SIV attenuated virus vaccine data suggest that the prolonged process for the development of protective vaccine immunity may be a general and distinguishing property of lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Animal lentiviral systems used as AIDS vaccine models have included simian/human immunodeficiency virus (SHIV)-monkey, simian immunodeficiency virus (SIV)-monkey, equine infectious anemia virus (EIAV)-horse, and feline immunodeficiency virus (FIV)-cat models (1). Interestingly, the greatest level of success has been realized with live attenuated animal lentivirus vaccines that are able to drive a critical maturation of virus-specific humoral and cellular immune responses (3,4,15,16,20,29,(36)(37)(38).…”
mentioning
confidence: 99%
“…Although two of the three long-term survivors have neutralizing antibodies against the challenge virus 2.5 years postchallenge, these antibodies were not detected at the time virus replication in the animals was being brought under control. In contrast to the neutralization test, other assays measuring the maturation of the binding antibody responses have suggested a better correlation with protection (8,9,34). It is possible that long-term resistance may be mediated by these kinds of antibodies in combination with memory effector CD8 ϩ T cells and CD4 ϩ T cells modulating the effectors.…”
Section: Cxcr4mentioning
confidence: 99%
“…Towards this objective of identifying differences in vaccine immunity in horses with and without detectable infection by challenge virus, we characterized quantitative and qualitative EIAV envelope-specific antibody responses that have previously been used to define the progression from immature non-protective vaccine immunity to mature protective vaccine immunity by attenuated lentiviral vaccines, including EIAV [1,2,39,43]. The results of these comparative serological assays including serum antibody titer, avidity, and conformation revealed a similar characteristic evolution of EIAV envelope-specific antibody responses in protected and unprotected horses during the first six months post inoculation with the EIAV D9 and during the following several months post-infection.…”
Section: Discussionmentioning
confidence: 99%